Балансово-оптимізаційна модель паливозабезпечення теплової енергетики на основі мережного подання варіантів роботи електричних станцій - Kaplin M.I.; Bilan T.R. (General Energy Institute of the National Academy of Sciences of Ukraine, 2018)
A network presentation of the economic-mathematical model of the choice of fuel supply options for thermal power is proposed with limited volumes of supplies of certain types of coal fuel. Variants of changes in the intensity of use of the installed capacity of electric power stations, the possibility of their conversion to alternative fuels are considered. The stream structure of supply chains of coal of various brand groups and corresponding ways of generation of electric energy is given. For this structure, the properties of the partially integer linear programming problem are explained, providing "switching" of the fuel supply chains depending on the need for electrical energy, the availability of the necessary volumes of fuel of the corresponding type.In the network presentation of fuel supply options and the functioning of TPPs and CHPPs, it is shown that the fuel balance of thermal power can be formed in conditions of structural changes in the extractive industries caused by the temporary occupation of part of the country's territory.The results of calculations of the predicted volumes of coal supplies to thermal power engineering, including the volumes of its import, are given in 2020 and 2025 when implementing measures planned for this period to convert part of the generating facilities to gas coal consumption, as well as coal mixes of different brand groups.